High Expression of Polo-Like Kinase 1 Is Associated with Early Development of Hepatocellular Carcinoma - Wei Sun; Qi Su; Xiankui Cao; Bin Shang; Aishan Chen; Hongzhuan Yin; Baolin Liu (International Journal of Genomics)
Polo-like kinase 1 (PLK1), one of serine/threonine-protein kinase, has been demonstrated to play pivotal roles in malignant transformation. Here we illustrated the clinicopathological significance of PLK1 expression in hepatocellular carcinoma (HCC) in more detail. Immunohistochemistry was performed to detect the expression of PLK1 in 67 HCC patients as well as corresponding noncancerous liver tissues. In addition, the correlation of PLK1 expression with clinicopathological factors or prognosis of HCC was analyzed. Results showed that the expression of PLK1 was increased significantly in HCC tissues than that of corresponding normal liver tissues. The correlation between PLK1 and HCC cell differentiation or capsule invasion was also revealed. We found that PLK1 inhibition promoted cell arrest in G2/M phase of cell cycle and cell apoptosis. Our results also indicated that the potential mechanisms of PLK1 inhibition regulating cell growth involved enhancing expression of caspase3, caspase8, and Bax and decreasing expression of Bcl-2. Furthermore, we also found that PLK1 downregulation inducing inhibition of cell growth was associated with enhancing expression of p53. Thus, we presume that the status of PLK1 expression might be an independent prognostic factor for HCC and targeting PLK1 might be a useful strategy for diagnosis and treatment of human HCC.